Manajemen Bimbingan Dan Konseling Di Sekolah - Setyo Pranoto (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2024)
Guidance and counseling teachers are guidance and counseling officers in schools who provide services related to student development and also making them independent. The implementation of guidance and counseling programs needs to be systematic and structured. Guidance and counseling management is needed to achieve the goals that have been created, because it can place the roles of guidance and counseling teachers in fulfilling their obligations to serve counselee, in this case students. Guidance and counseling management includes planning, organizing, actuating or implementation and also controlling and monitoring or what is called supervision, which is the core of management in guidance and counseling in schools. The role of guidance and counseling teachers in guidance and counseling management is very important, sothe expertise of guidance and counseling personnel is needed to carry out good management. Good management carried out by good personnel can facilitate achieving the desired goals.